2006
DOI: 10.1038/sj.npp.1300992
|View full text |Cite
|
Sign up to set email alerts
|

Higher 5-HT1A Receptor Binding Potential During a Major Depressive Episode Predicts Poor Treatment Response: Preliminary Data from a Naturalistic Study

Abstract: Serotonin 1A (5-HT 1A ) binding potential (BP) as assessed by positron emission tomography (PET) is higher in major depressive disorder (MDD) in association with the higher expressing GG genotype of the 5-HT 1A C-1019G polymorphism. We hypothesize that higher 5-HT 1A BP and the GG genotype predict remission failure on antidepressant treatment. We determined 5-HT 1A BP by PET and 5-HT 1A C-1019G genotype in 43 controls and 22 medication-free MDD subjects. MDD was treated naturalistically and remission was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(133 citation statements)
references
References 18 publications
6
124
0
3
Order By: Relevance
“…Recent PET imaging studies in humandepressed patients show an association of rs6295 with an increase in raphe 5-HT 1A binding potential. A significant association was observed in unmedicated or antidepressant-naive depressed patients [102]. In this cohort, the rs6295 risk allele and genotype also associated with depression.…”
Section: Association Of Rs6295 With Altered 5-ht 1a Receptor Expressimentioning
confidence: 67%
See 1 more Smart Citation
“…Recent PET imaging studies in humandepressed patients show an association of rs6295 with an increase in raphe 5-HT 1A binding potential. A significant association was observed in unmedicated or antidepressant-naive depressed patients [102]. In this cohort, the rs6295 risk allele and genotype also associated with depression.…”
Section: Association Of Rs6295 With Altered 5-ht 1a Receptor Expressimentioning
confidence: 67%
“…An increase in 5-HT 1A autoreceptor expression has been reported in the rostral raphe region of post-mortem tissue from a depressed suicide victim compared with control subjects, but with reduced 5-HT 1A autoreceptor levels in caudal raphe regions [99,100]. Positron emission tomography (PET) imaging studies in living depression patients using the 5-HT 1A antagonist [ 11 C]WAY100635 also show a prominent 50 per cent increase in 5-HT 1A autoreceptors in antidepressant-free or naive depressed subjects [101][102][103], as well as a twofold increase in male bipolar depression patients [104]. An upregulation of 5-HT 1A autoreceptors is likely to reduce serotonergic neurotransmission, as associated with human depression and suicide ( figure 1).…”
Section: Implications Of 5-ht 1a Autoreceptor Dysregulation For Mentamentioning
confidence: 99%
“…We have previously found that 5-HT 1A receptor binding is elevated in non-remitters compared to remitters and controls, and demonstrated an association between a polymorphism in the 5-HT 1A promoter and remission status (Parsey et al, 2006c). Combining imaging and genetic variables for 5-HTT and 5-HT 1A in a statistical model may allow us to account for a greater degree of the variance in treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The log transform was necessary because of two features of our BP P data: skewness, and unequal standard deviation (SD) of measurements across groups with different binding levels (with SD roughly proportional to the binding level). We and others have used this or related statistical approaches to allow for valid statistical analysis of PET data with these characteristics (Meltzer et al, 2004;Oquendo et al, 2006;Parsey et al, 2006a;Parsey et al, 2006b;Parsey et al, 2006c;Parsey et al, 2006d;Rabiner et al, 2002;Sullivan et al, 2005). Graph of binding potential (Figures 1 and 2) uses actual (not log-transformed) BP P values.…”
Section: Statisticsmentioning
confidence: 99%
“…Based on our results, the human 5-HT1A G/G(Ϫ1019) genotype would be predicted to result in opposite changes in 5-HT1A receptor RNA and protein levels in pre-and postsynaptic brain regions. Recent studies support an up-regulation of 5-HT1A autoreceptors in antidepressant-free depressed patients with the G/G genotype (21,22,50), but not in healthy subjects (51). This suggests that compensatory mechanisms may be recruited in healthy subjects to normalize 5-HT1A autoreceptor expression whereas they are incompletely effective in depressed subjects.…”
Section: Altered 5-ht1a Receptor Expression In Deaf-1 Knock-outmentioning
confidence: 97%